2016
DOI: 10.4172/2161-069x.c1.047
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Her2/neu expression in colorectal adenocarcinoma: A study from developing South Asian country

Abstract: Background: Human Epidermal Growth Factor (Her-2/neu) has strong therapeutic implications in certain cancers like breast and gastric cancer. Literature on its frequency in colorectal cancer is scarce. In this study, we have investigated the frequency of Her-2/neu expression in colorectal adenocarcinomas and its association with various clinicopathological variables. Methods: A total of 95 patients who underwent colonoscopic biopsy or colectomy were studied after Institutional Ethical Approval. Hematoxylin & eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In agreement with Song et al, (2014), Shabbir et al, (2016) and Sayadnejad et al, (2017) we did not find a significant link between HER2 expression and tumor stage or lymph node metastasis (TN stage). On the contrary, Elwy et al, (2012) and Heppner et al, (2014) reported a significant association with higher stages and positive nodal status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with Song et al, (2014), Shabbir et al, (2016) and Sayadnejad et al, (2017) we did not find a significant link between HER2 expression and tumor stage or lymph node metastasis (TN stage). On the contrary, Elwy et al, (2012) and Heppner et al, (2014) reported a significant association with higher stages and positive nodal status.…”
Section: Discussionsupporting
confidence: 93%
“…Half and his colleagues, 2004 found a significant relation between the cytoplasmic HER2 staining and tumor differentiation. Also, Shabbir et al, (2016) concluded a significant strong association between cytoplasmic HER2 expression and low grades of CRC, as well as between membranous HER2 expression and high grade CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the IRS-p ranges from 0 to 9, while the IRS-m ranges from 0 to 24. Then, both IRS-p and IRS-m were classi ed into IHC 1+ (IRS-p score 1-2, IRS-m score 1-3), IHC 2+ (IRSp score 3-7, IRS-m score 4-8), and IHC 3+ (IRS-p score 8-9, IRS-m score [12][13][14][15][16][17][18][19][20][21][22][23][24]. IHC scores of 0 and 1+ were considered as being "HER2 negative", IHC score of 2+ was considered as being "HER2 equivocal", and IHC score of 3+ was considered as being "HER2-positive".…”
Section: Her2 Ihc Scoring Methodsmentioning
confidence: 99%
“…They de ned three conditions of HER2 positivity as follows (HERACLES criteria): (1) a HER2 immunohistochemical (IHC) 3 + score in ≥ 50% of CRC cells; (2) a HER2 IHC 3 + score in 10%-50% of the CRC cells, and a uorescence in situ hybridization (FISH) HER2/CEP17 ≥ 2.0 in ≥ 50% of CRC cells; (3) more than 50% of CRC cells with a HER2 IHC 2 + score and a FISH HER2/CEP17 ≥ 2.0. However, to date, HER2 diagnostic criteria for gastroesophageal adenocarcinoma (GEA criteria) 16 or other independent HER2 IHC scoring systems 21,22 have also been used in CRC HER2 studies. Moreover, the prognostic role of HER2 in CRC remains controversial.…”
Section: Introductionmentioning
confidence: 99%